Inclusive leadership: memperkuat employee work engagement dan affective organizational commitment di perusahaan furnitur - Purwoasih, Elgie; Nugrohoseno, Dwiarko (Universitas Negeri Surabaya, 2024)
This study aims to test and analyze the effect of inclusive leadership on employee work engagement through affective organizational commitment in PT. XXX. The approach used in this study is quantitative. The sampling technique used saturated sampling with a total of 44 employees. The data in this study were analyzed using the Structural Equation Model Partial Least Square (SEM-PLS) with SmartPLS 4.1.0.3 software. The result showed that inclusive leadership has a positive effect on employee work engagement, inclusive leadership does not effect affective organizational commitment, affective organizational commitment has a positive effect on employee work engagement, affective organizational commitment does not mediate the relationship between inclusive leadership and employee work engagement. This research implies the need for PT. XXX to increase its focus on employee work engagement through strengthening inclusive leadership and affective organizational commitment.